2013
DOI: 10.3109/15412555.2013.825593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pursed-Lip Breathing in Patients With COPD: Linear and Nonlinear Analysis of Cardiac Autonomic Modulation

Abstract: PLB led to a loss of fractal correlation properties of heart rate in the direction of linearity in patients with COPD as well as an increase in vagal activity and impact on the spectral analysis. The difference in the magnitude of the changes produced by PLB between groups may be related to the presence of the disease and alterations in the respiration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
3
25
0
3
Order By: Relevance
“…Lower frequencydomain values were reported in some studies for LF, 3 10,34,38,44 and HFnu in subjects with COPD compared with their healthy counterparts. 10,34,38,44 Additionally, higher values were reported in a few studies for LF, 40 HF, 40 LF/HF, 43 and HFnu 39 in subjects with COPD compared with healthy controls.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 91%
See 1 more Smart Citation
“…Lower frequencydomain values were reported in some studies for LF, 3 10,34,38,44 and HFnu in subjects with COPD compared with their healthy counterparts. 10,34,38,44 Additionally, higher values were reported in a few studies for LF, 40 HF, 40 LF/HF, 43 and HFnu 39 in subjects with COPD compared with healthy controls.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 91%
“…Fifteen studies of high methodological quality investigated the differences in heart rate variability values between subjects with COPD and healthy controls. 3,10,13,19,[34][35][36][37][38][39][40][41][42][43][44] Most of these studies reported significantly lower heart rate variability in subjects with COPD. Specifically, the time-domain parameters in most of the studies (12 of 15) showed that subjects with COPD had lower heart rate variability compared with healthy controls.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 99%
“…It has been applied to the evaluation of posture [17], exercise [18] and sleep stage classification [19], and classification of asthma [20] and COPD [16,21,22].…”
Section: Detrended Fluctuation Analysis (Dfa)mentioning
confidence: 99%
“…Eight articles were further excluded for failure to meet all the inclusion criteria. In the end, 18 studies comprising eleven case-controlled, 6,8,10,15,22,[35][36][37][38][39]41 four cohort, 5,19,27,40 and three RCT 20,23,28 studies were included for evidence synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
“…The respiratory rehabilitation techniques reported in the studies included oxygen supplementation (six studies), 8,19,20,39,35,36 NIMV (five studies), 5,22,23,37,40 and controlled breathing techniques (eight studies) in form of slow breathing, 8,10 purse lip breathing, 27,38 resistive loading, 15 and breathing maneuvers. 6,28,41 Only three AF outcomes were reported in the included studies.…”
Section: Study Characteristics and Outcome Measuresmentioning
confidence: 99%